Gut microbiota and short-chain fatty acids may be new biomarkers for predicting neonatal necrotizing enterocolitis: A pilot study - Liu, Xiao-Chen; Du, Ting-Ting; Gao, Xiong; Zhao, Wen-Jing; Wang, Zheng-Li; He, Yu; Bao, Lei; Li, Lu-Quan (Frontiers in Microbiology, 2022)
Background Dysbacteriosis is thought to play an important role in the pathogenesis of necrotizing enterocolitis (NEC). We aimed to identify new biomarkers among gut microbiota and short-chain fatty acids (SCFAs) for the early prediction of NEC. Materials and methods Thirty-four preterm infants with gestational ages of ≤ 34 weeks who developed gastrointestinal symptoms were divided into the NEC group (n = 17) and non-NEC group (n = 17). In the NEC group, the gut microbiota and SCFAs in feces were assessed when the infants were enrolled (Group P) and when they were diagnosed with NEC (Group N). In the non-NEC group, samples were assessed when the infants were enrolled (Group C). Results The Ace and Chao1 indices were higher in Group P than in Group C (P < 0.05), and there was no difference between Groups C and N or between Groups P and N (P > 0.05). There was no significant difference in the Simpson and Shannon indices among Groups C, P and N (P > 0.05). The four main phyla showed no differences (P > 0.05) in composition, while at the genus level, compared with Group C, in Group P, Clostridioides, Blautia and Clostridium_sensu_stricto_1 were increased, while Lactobacillus and Bifidobacterium were decreased (P < 0.05). At the species level, Streptococcus salivarius and Rothia mucilaginosa increased, while Bifidobacterium animals subsp. lactis decreased (P < 0.05). In Group N, at the genus level, Stenotrophomonas, Streptococcus and Prevotella increased (P < 0.05). Compared with those in Group C, the levels of acetic acid, propanoic acid and butyric acid decreased significantly in Groups P and N (P < 0.05), and the areas under the curves (AUCs) of these three SCFAs between groups C and P were 0.73, 0.70, and 0.68, respectively. Conclusion The increase in Streptococcus salivarius and Rothia mucilaginosa and decrease in Bifidobacterium_animals_subsp._lactis, as well as the decrease in acetic, propionic and butyric acids, may help in the early prediction of NEC.